Spatiotemporal distribution of methane concentration from broken coal mass - Sizin Pavel; Zakorshmennyi Iosif; Blokhin Dmitry; Kobylkin Alexander; Dianov Peter (EPJ Web of Conferences)
The paper proposes a mathematical model, based on a one-dimensional nonhomogeneous diffusion equation, which enables the evaluation of methane emissions from extracted coal during its transportation through the haulage system of a coal mine longwall face and their contribution to spatiotemporal distribution patterns of mine atmospheric parameters characterizing the gas environment in the face area. The solution to the specified equation has been implemented using the Mathcad computational software package. The results of numerical experiments demonstrate potential applicability for enhancing operational efficiency in managing technological processes within the boundaries of the longwall face.